The Effectiveness of the Annual Notification Letter E-Form Service for Business Taxpayers at KP2KP Sinjai Regency - Umar Congge; Fitrawati Fitrawati (Jurnal Ad'ministrare, 2023)
Taxes are obligatory contributions of the people to the state that are coercive and do not receive compensation services that are directly used to finance state expenditures. The purpose of this study was to determine the effectiveness of the annual SPT E-form service for business taxpayers at the KP2KP Sinjai Regency and to determine the inhibiting factors and supporting factors for the annual SPT E-form service for business taxpayers at the KP2KP Sinjai Regency. This research is a qualitative research using data collection techniques through observation, interviews, questionnaires and documentation. As for the data analysis techniques used, namely, data reduction, data presentation and verification/conclusion. The results of this study can be concluded that the effectiveness of the Annual SPT E-form Service for Business Taxpayers at KP2KP Sinjai Regency the effectiveness of the E-form service (Program Understanding) that the ability of employees to provide program understanding services is very good. This research can be used as a reference source regarding the annual SPT E-form service for business taxpayers because previous research has discussed more about the Annual SPT E-Form service for personal taxpayers